Proceedings of the 9th International Joint Conference on Biomedical Engineering Systems and Technologies 2016
DOI: 10.5220/0005774603710376
|View full text |Cite
|
Sign up to set email alerts
|

Deployment of ARCS Model and Utilization of Communication Robot in Patient Education

Abstract: Medication non-compliance" is a failure to take medication properly. Therefore, medication is necessary for patients to be able to understand medication properly and to participate in treatment voluntarily with the right motivation. For this study, we design medication education based on the ARCS model(Attention, Relevance, Confidence, Satisfaction), which classifies concepts related to learning motivation (Keller, 1984), and which incorporates utilization of the communication robot "Pepper".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…“Communication” was the least‐expected role for robots and the topic was of some concern, as revealed by the open‐ended question. Although some robots that react to different stimuli and recognize emotions have been used therapeutically in hospitals, including the humanoid robot Pepper and the therapeutic pet robot Paro (Yu et al., ; Ishiguro & Majima, ), improvements in accurate interpretation of complex emotions are necessary in guardian‐free environments. Care robots may not facilitate communication between nurses and patients and indeed may also not aid communication among medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…“Communication” was the least‐expected role for robots and the topic was of some concern, as revealed by the open‐ended question. Although some robots that react to different stimuli and recognize emotions have been used therapeutically in hospitals, including the humanoid robot Pepper and the therapeutic pet robot Paro (Yu et al., ; Ishiguro & Majima, ), improvements in accurate interpretation of complex emotions are necessary in guardian‐free environments. Care robots may not facilitate communication between nurses and patients and indeed may also not aid communication among medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Japan, robots have been used to support health education programmes. 61 Previous studies have demonstrated that social robotics can benefit language and social development in autistic children, 62 presenting an opportunity for robots to facilitate education in wider society to promote better understanding of palliative care. Robots also have the potential to support palliative care training for healthcare professionals by creating immersive learning environments through the use of virtual reality.…”
Section: Opportunities In Palliative Carementioning
confidence: 99%
“…While most of the included studies fully met the inclusion criteria, some partially deviated. Three studies (Bedaf et al, 2018;Feingold-Polak et al, 2018;Ishiguro et al, 2016) focused on both younger and older persons. Two studies (Abdollahi et al, 2017;Ikeya et al, 2018) did not explicitly mention the persons' ages, but upon reading, it emerged that their target groups were older persons with severe dementia.…”
Section: Resultsmentioning
confidence: 99%
“…In three studies (Feingold-Polak et al, 2018;Ishiguro et al, 2016;Orejana et al, 2015), HRs were investigated with regard to their ability to facilitate cognitive training for older persons. Orejana et al (2015) studied the feasibility and usefulness of using HRs to support older persons living alone to manage their medication, using an HR that, e.g., facilitated entertainment and played memory games.…”
Section: Category 3 Facilitates Cognitive Trainingmentioning
confidence: 99%
See 1 more Smart Citation